Investigation of the safety and protective efficacy of an attenuated and marker M. bovis-BoHV-1 combined vaccine in bovines - Zhang, Sen; Liu, Guoxing; Zhang, Yisheng; Wang, Chen; Xu, Xiaowen; Zhao, Yuhao; Xiang, Zhijie; Wu, Wenying; Yang, Li; Chen, Jianguo; Guo, Aizhen; Chen, Yingyu (Frontiers in Immunology, 2024)
Bovine respiratory disease (BRD) is one of the most common diseases in the cattle industry worldwide; it is caused by multiple bacterial or viral coinfections, of which Mycoplasma bovis (M. bovis) and bovine herpesvirus type 1 (BoHV-1) are the most notable pathogens. Although live vaccines have demonstrated better efficacy against BRD induced by both pathogens, there are no combined live and marker vaccines. Therefore, we developed an attenuated and marker M. bovis-BoHV-1 combined vaccine based on the M. bovis HB150 and BoHV-1 gG-/tk- strain previously constructed in our lab and evaluated in rabbits. This study aimed to further evaluate its safety and protective efficacy in cattle using different antigen ratios. After immunization, all vaccinated cattle had a normal rectal temperature and mental status without respiratory symptoms. CD4+, CD8+, and CD19+ cells significantly increased in immunized cattle and induced higher humoral and cellular immune responses, and the expression of key cytokines such as IL-4, IL-12, TNF-α, and IFN-γ can be promoted after vaccination. The 1.0 × 108 CFU of M. bovis HB150 and 1.0 × 106 TCID50 BoHV-1 gG-/tk- combined strain elicited the most antibodies while significantly increasing IgG and cellular immunity after challenge. In conclusion, the M. bovis HB150 and BoHV-1 gG-/tk- combined strain was clinically safe and protective in calves; the mix of 1.0 × 108 CFU of M. bovis HB150 and 1.0 × 106 TCID50 BoHV-1 gG-/tk- strain was most promising due to its low amount of shedding and highest humoral and cellular immune responses compared with others. This study introduces an M. bovis-BoHV-1 combined vaccine for application in the cattle industry.